Combination of Superficial and Deep Blocks with Rivaroxaban. Issue 10 (14th July 2015) - Chelly, Jacques E.; Metais, Benjamin; Schilling, Dennis; Luke, Charles; Taormina, Darrin
Abstract: Objective: Rivaroxaban is a new Xa inhibitor indicated for thromboprophylaxis in patients undergoing joint arthroplasty. This study was designed to assess the risk of major bleeding from the combination of either a single or a continuous deep, superficial, and plexus block and the use of rivaroxaban for thromboprophylaxis following joint arthroplasty. Method: Patients undergoing either primary, redo, unilateral, or bilateral total hip or knee replacement while receiving a femoral, sciatic, lumbar plexus nerve block alone or in combination and receiving at least one dose of rivaroxaban 10 mg once a day for thromboprophylaxis postoperatively were included in this analysis. Results: In this series, 766 patients (199 total hip replacements and 567 total knee replacements) were included. A total of 1, 104 blocks were performed including 1, 029 continuous blocks (509 femoral, 320 sciatic, and 200 lumbar plexus). No major bleeding related to the performance of peripheral nerve blocks was recorded. In contrast, three patients developed hematomas in the operated knee requiring a surgical evacuation. Minor bleeding was recorded at the surgical site in 12 patients vs 10 patients at the site of the block. Although all minor bleeding at the surgical site occurred after the initiation of the rivaroxaban therapy, 80% of minor bleeding at the site of the block was recorded before the initiation of thromboprophylaxis. Conclusion: Our data supports the concept that there is no increased risk of major bleeding when deep and superficial blocks are performed in combination in patients receiving thromboprophylaxis rivaroxaban following joint arthroplasty.